Age Induced Nitroso-Redox Imbalance Leads to Subclinical Hypogonadism in Male Mice - Lee, John Alden; Kuchakulla, Manish; Arora, Himanshu; Kulandavelu, Shathiyah; Gonzalez, Evert; Masterson, Thomas A.; Hare, Joshua M.; Kaiser, Ursula B.; Ramasamy, Ranjith (Frontiers in Endocrinology, 2019)
Objective: The cause of age-related changes in testosterone remains unclear. We hypothesized that increased nitroso-redox imbalance with aging could affect testosterone production. Materials and Methods: We determined several markers of nitroso-redox imbalance (4-HNE, NT, and 3-NT) in serum of S-nitrosoglutathione reductase knock out (GSNOR KO) mice that have increased nitroso-redox imbalance and compared these to WT mice. We evaluated the impact of age-induced nitroso-redox imbalance on serum luteinizing hormone (LH) and testosterone (T) in WT at pre-pubertal (<2 months), middle-aged (2-6 months), and aged (>12 months) mice. Finally, to elucidate the susceptibility of testes to nitroso-redox imbalance, we measured HNE expression in WT and KO mice. Results: We identified 4-HNE as a reliable marker of nitroso-redox imbalance as evidenced by increased expression in serum of GSNOR KO mice compared with WT mice. We demonstrated that 4-HNE expression in serum increases in WT mice with age and does not accumulate in the testes. We also identified that testosterone levels were similar in all age groups. Interestingly, we found that serum LH levels in aged and middle-aged mice were increased when compared to pre-pubertal mice (n=5) consistent with the phenotype of subclinical hypogonadism. Conclusions: Increasing 4-HNE expression with age suggests that nitroso-redox imbalance is a likely mechanism for subclinical hypogonadism. Recognizing the relationship and etiology of a currently poorly understood classification of hypogonadism could be a paradigm shift in how age-related testosterone change is diagnosed and treated.